2023
DOI: 10.22541/au.167492196.63331819/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcium oxalate crystal macropattern and its usefulness in the taxonomy of Baccharis (Asteraceae)

Abstract: This study provides a comprehensive account of the various types of calcium oxalate crystals found in the genus Baccharis and assesses the exceptional value of crystal macropatterns for the taxonomy of the genus. The morphotype, occurrence and chemical composition of the crystals found in the stems and leaves are studied. The 44 species included in this study were selected based on a broad phylogeny-based sampling covering seven subgenera and 31 sections. These species were chosen to represent all the main phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Simple non-glandular trichomes as observed in the present work have been reported for several genera of Asteraceae family, such as Baccharis [1,4,15], Calea [14 ] and Solidago [18]. The presence of crystals in trichomes is an additional characteristic helpful in species identification [20]. The occurrence of crystals in trichomes was previously mentioned in some members of the family Asteraceae including Baccharis punctulata DC.…”
Section: Resultssupporting
confidence: 80%
“…Simple non-glandular trichomes as observed in the present work have been reported for several genera of Asteraceae family, such as Baccharis [1,4,15], Calea [14 ] and Solidago [18]. The presence of crystals in trichomes is an additional characteristic helpful in species identification [20]. The occurrence of crystals in trichomes was previously mentioned in some members of the family Asteraceae including Baccharis punctulata DC.…”
Section: Resultssupporting
confidence: 80%
“…It is characterized by having a pointed end and the opposite end with a "V" shaped indentation, resembling the tip of an arrow [22].…”
Section: Arrow Shapedmentioning
confidence: 99%
“…Anatomical studies are very relevant because they unravel key traits that help differentiate species (Cutter, 2002; Metcalfe & Chalk, 1950; Stuessy, 2009). A number of recent studies have reported the importance of microscopic features in, for example, the authentication and quality control of species of ethnomedicinal interest and in taxonomy (Antunes et al, 2023; Raeski et al, 2023). In the case of Convolvulaceae, anatomical studies have provided valuable data to support the taxonomy of the family.…”
Section: Introductionmentioning
confidence: 99%